2013
DOI: 10.1016/j.taap.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

In vivo application of a small molecular weight antifungal protein of Penicillium chrysogenum (PAF)

Abstract: The small antifungal protein secreted by Penicillium chrysogenum (PAF) inhibits the growth of important zoo pathogenic filamentous fungi, including members of the Aspergillus family.It was shown previously that PAF has no toxic effects on mammalian cells in vitro. We carried out safety experiments by investigating the in vivo effects of PAF by inoculating adult C57/B16 mice with PAF intranasally. Animals were randomly divided into six groups and subjected to different PAF concentrations, up to 54 µg, either on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…These natural proteins inhibit the growth of human-, animal- and plant-pathogenic moulds [8]. No detrimental effects on plant or on mammalian cells in vitro and in vivo could be observed for PAF [9, 10] and AFP [11, 12]. These findings strongly support their applicability as new antifungal drugs or their use for the development of new antifungal strategies.…”
Section: Introductionmentioning
confidence: 88%
“…These natural proteins inhibit the growth of human-, animal- and plant-pathogenic moulds [8]. No detrimental effects on plant or on mammalian cells in vitro and in vivo could be observed for PAF [9, 10] and AFP [11, 12]. These findings strongly support their applicability as new antifungal drugs or their use for the development of new antifungal strategies.…”
Section: Introductionmentioning
confidence: 88%
“…6 It was previously observed that PAF can effectively inhibit the growth of numerous filamentous fungi causing membrane permeabilization, intracellular oxidative stress, and evoking programmed cell death through a G‐protein signal‐transduction pathway 7. PAF is harmless for mammals, as proven in our recent PET (positron emission tomography) experiments 8. Therefore, PAF is promising for the treatment of mycoses and fungal infections, especially against aspergillosis.…”
Section: Introductionmentioning
confidence: 92%
“…It is a prepro-protein which is processed before secretion and the mature PAF consists of 55 amino acids (Fig 1A) [4]. It specifically inhibits the growth of opportunistic human- and plant-pathogens, such as Aspergillus fumigatus and Botrytis cinerea , but is inactive against mammalian cells both in vitro and in vivo [5,6]. In the course of our intensive studies to understand the mechanistic action of PAF, we have investigated its solution structure in great detail [7,8].…”
Section: Introductionmentioning
confidence: 99%